First described case of self-inflicted injury in a brown bear (Ursus arctos Linnaeus, 1758) following capture with an Aldrich snare - Vladimir R. Todorov; Angel Dyugmedzhiev (Historia naturalis bulgarica, 2023)
Trapping bears (Ursidae) with Aldrich leg snares has established itself as one of the most successful methods of trapping live animals with minimal injury. Most documented injuries are related to damage caused by the trap and prolonged exposure to it. Various physiological and behavioural responses have been observed, however self-eating of the toes of the captured foot has not been described so far. In November 2017 an adult male brown bear was caught with a standard Aldrich type leg snare. When the research team arrived, the bear teared off and swallowed phalanges of the first toe of its rear left foot before it could be sedated. The bear was measured and marked with GPS-GSM collar. Following the instalment of the collar, the animal was monitored for the duration of 23 months when the drop-off mechanism of the collar was activated. This rule out the possibility that a serious life threatening complications arised from the trauma.